How does the propensity of living near rail transit moderate the influence of rail transit on transit trip frequency in Xi'an?. (June 2016) - Huang, Xiaoyan; Cao, Xinyu (Jason); Cao, Xiaoshu; Yin, Jiangbin
Abstract: Many cities have made massive investments on rail systems to substitute transit for driving. Some studies have considered the confounding effect of attitudes in the connections between rail transit and travel behavior. However, they often focused on the average effect of rail transit and assumed that individuals' responses to transit improvements do not vary by their tastes. Using the 2014 data from Xi'an in China, this study explores the interaction effect between metro transit (heavy rail) and the propensity (i.e., predicted probability) of living in neighborhoods with metro transit on transit use. The propensity is positively associated with commute by metro transit and bus. Further, individuals with a strong propensity use transit equivalently no matter whether they live near metro transit, but metro transit tends to promote transit commute for those with a weak propensity of living near metro transit. Overall, building a rail line helps enhance transit ridership. Planners should also consider the variation in responses by individuals with different tastes when using policies to shape urban travel. Highlights: It isolates the impacts of rail transit and neighborhood characteristics. The effects of metro transit rely on the propensity of living near transit. The travel propensity dominates transit us. Metro transit promotes transit commute of station area residents..